Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1051/0004-6361/201323292
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit angle distribution and the origin of (mis)aligned hot Jupiters

Abstract: Context. For 61 transiting hot Jupiters, the projection of the angle between the orbital plane and the stellar equator (called the spinorbit angle) has been measured. For about half of them, a significant misalignment is detected, and retrograde planets have been observed. This challenges scenarios of the formation of hot Jupiters. Aims. In order to better constrain formation models, we relate the distribution of the real spin-orbit angle Ψ to the projected one β. Then, a comparison with the observations is re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…In this frame, the observed misalignment of approximately half of the hot Jupiters with respect to the stellar equator could be the result of a misalignment between the old disc midplane and the present stellar equator (see for instance Crida & Batygin 2014).…”
Section: Hot Jupitersmentioning
confidence: 97%
“…In this frame, the observed misalignment of approximately half of the hot Jupiters with respect to the stellar equator could be the result of a misalignment between the old disc midplane and the present stellar equator (see for instance Crida & Batygin 2014).…”
Section: Hot Jupitersmentioning
confidence: 97%
“…Whereas first observed systems revealed aligned, prograde orbits (e.g., Queloz et al 2000;Winn et al 2005;Loeillet et al 2008), first misaligned systems were reported with the cases of XO-3 (Hébrard et al 2008;Winn et al 2009c;Hirano et al 2011) and HD 80606 (Moutou et al 2009;Pont et al 2009;Winn et al 2009a;Hébrard et al 2010). About thirty misaligned systems have been identified today over more than eighty measured systems 1 (Albrecht et al 2012;Crida & Batygin 2014), including some with retrograde or nearly polar orbits (e.g., Winn et al 2009b;Narita et al 2010;Triaud et al 2010;Hébrard et al 2011). These unexpected results favor scenarios where close-in massive planets have been brought in by planet-planet (or planet-star) scattering, Kozai migration, and/or tidal friction, rather than more standard scenarios implying disk migration that are expected to conserve the initial alignment between the angular momentums of the disk and of the planetary orbits (see, e.g., Fabrycky & Tremaine 2007;Guillochon et al 2011), although some models show that the initial misalignment of a planet can be maintained through its interactions with the disk (Teyssandier et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms take place after the dispersal of the protoplanetary disk and can lead to highly inclined planets. To date, it is debated whether disk migration or scattering/Kozai is the dominant mechanism leading to close-in planets (e.g., Crida & Batygin 2014). …”
Section: Introductionmentioning
confidence: 99%